Osimertinib-Induced Cardiomyopathy - Shruti R. Patel, MD; Sherry-Ann N. Brown, MD, PhD; Jilan E. Kubusek, PharmD, RPh; Aaron S. Mansfield, MD; Narjust Duma, MD (JACC: Case Reports, 2020)
Osimertinib is the preferred treatment in patients with metastatic non–small cell lung cancer with epidermal growth factor receptor mutations. We report a case series of acute cardiomyopathy with heart failure exacerbation during osimertinib treatment. We suggest that cardiotoxicity from osimertinib is reversible and occurs at a dose of 80 mg/day. (Level of Difficulty: Intermediate.)